Coronary angiographic findings in patients with chest pain and right bundle branch block - Abid, Ihssan A.; Al Doori, Kassim M. J.; Al Myahi, Mohammed H. (Journal of the Faculty of Medicine Baghdad, 2008)
Back ground : Coronary artery diseases are not uncommon in the presence of right bundle branch block. Aim : The aim of this study is to assess the findings of coronary angiography in patients with chest pain and right bundle branch block. Methods : The study involved review of case sheets and coronary angiography of one hundred patients, who underwent coronary angiography due to chest pain suspected to have coronary artery diseases (CAD) , fifty patients of them had right bundle branch block (RBBB) , the other fifty did not have RBBB , those 100 patients were presented to Ibin Al Bitar hospital for cardiac surgery from January 2004 to June 2006. History, clinical examinations, electrocardiogram (ECG) , ECG exercise tests (EET) echocardiogram (ECHO) and coronary angiography had been performed. Results : Mean age of patients was 53± 10.6 years, 84% were male , hypertension, diabetes mellitus, and smoking as risk factors were present as 30%, 32% and 48% respectively. 58% of patients presented with chronic stable angina (CSA) while 42% with acute coronary syndrome (ACS), ECHO showed that left ventricular dysfunction (LVD) was present in 34%, EET was positive in 11 of the 23 patients (47.8%) who were able to perform EET. Normal coronary angiography found in 20% of patients and there were no significant difference in coronary angiographic findings between patients with and without RBBB. Conclusion : RBBB of indeterminate age has no significant impact on clinical and haemodynamic characteristics of CAD patients and it may be incidental finding.